Children's distal forearm fractures: a population- based epidemiology study of 4, 316 fractures. (2022) - Korup, L. R.; Larsen, P.; Nanthan, K. R.; Arildsen, M.; Warming, N.; Sørensen, S.; Rahbek, O.; Elsoe, R.
No abstract available